An integrative review of assessments used in occupational therapy interventions for children with cerebral palsy/Revisão integrativa de avaliações utilizadas em intervenções de terapia ocupacional para crianças com paralisia cerebral - Peters, Carly; Chang, Amy; Morales, Abbiagail; Barnes, Karin; Alegretti, Ana (Cadernos Brasileiros de Terapia Ocupacional, 2019)
Introduction: Children with cerebral palsy (CP) experience a wide range of deficits and symptoms. When undergoing occupational therapy (OT) interventions, it is essential that the OT select assessments that can accurately reflect the outcome measures of the targeted domains. Objective: To identify the assessment tools most frequently reported in research studies as measures for OT interventions when treating children with CP. Method: Pubmed and Ovid databases were systematically searched by using key terms “cerebral palsy,” “assessments,” and “occupational therapy”. Assessment tools were explored and extracted from articles contingent on the following inclusion criteria: (1) children birth to 18 years diagnosed with cerebral palsy; (2) use of assessment(s) as a measure of OT intervention; (3) published in English between 2007 and 2017. In the preliminary search, Pubmed yielded 151 records and Ovid yielded 571. Out of these, only 76 met the inclusion criteria. From the remaining 76 articles, a total of 88 assessment tools were retrieved and included in this literature review. Results: Ten assessments were found to be of importance based on frequency of use. The Assisting Hand Assessment (AHA) and Pediatric Evaluation of Disability Inventory (PEDI) were the most commonly used. Conclusion: This study helps to determine which assessments are frequently used in OT practice with children with CP. The findings of this study play an important role in addressing the challenge of assessment selection faced by occupational therapists and provide a basis for future research to expand on with regards to treating children with CP.